The Bibliographic studies on Scolopendra subspinipes mutilans L. Koch - Go, Gang-Hun; So, Gi-Suk; Choe, Hoe-Gang; O, Hui-Hong; Kim, Il-Du; Park, Sang-Jun; An, Su-Gi; Kim, Seong-Cheol; Park, So-Yeong (Korean Pharmacopuncture Institute, 2002)
Objective: Through the literature on the effect of Scolopendra subspinipes mutilans L. Koch, we are finding out the clinical possibility and revealing the more effective to untractable disease. Method: We investigated the literatures of Oriental Medicine and experimental reports about Scolopendra subspinipes mutilans L. Koch. Results: 1.The taste of Scolopendra subspinipes mutilans L. Koch is hot, wann and toxic, and the effect is dispelling wind, spasmolytic action and detoxication so it has been used for C.V.A, facial palsy, numbness of hands and feet, wounds and arthritis. 2. A toxic constituent of Scolopendra subspinipes mutilans L. Koch is mainly located in the 1st limbs, and we can prevent toxic symptoms, if taken a dosage moderately. 3. The pharmacological action of Scolopendra subspinipes mutilans L. Koch is anti-convulsive action, analgesic action, lowering blood pressure, anti-inflammatory action, anti-tumor action and microbe inhibition. On the study of Scolopendra subspinipes mutilans L. Koch, we thought it is effective to intractable disease, and it may be needed variable studies on toxicity and clinical effects.